Seismic Performance Evaluation of Reinforced Concrete Building in Palu City - Fajar Nugroho; Jafril Tanjung; Maidiawati Maidiawati; Ruddy Kurniawan (Universitas Islam 45, 2024)
The earthquake accompanied by a tsunami that occurred in Palu City in 2018 resulted in damage, especially reinforced concrete buildings, one of which was the FISIP Dean Building, Tadulako University. This study aims to evaluate the seismic performance of the building using SeismoStruct software. This software is able to predict the behaviour of large displacements of space frames under static or dynamic loading by considering geometric nonlinearity and material inelasticity. Building modelling is made based on Detail Engineering Design drawings. The results of the analysis in the form of a capacity curve show that the building's performance is at the life safety level, which means that structural components are damaged so that the building's strength is reduced. There are two types of building collapse mechanisms that occur, namely yielding in the reinforcement (yield) and collapse in the concrete cover (crush-unconfined). Collapse occurred in the column where it should have occurred in the beam.